Polydiacetylene and imidazole mixed self-standing films for colorimetric detection of various volatile organic analytes. (October 2019) - Suklabaidya, Sudip; Chakraborty, S; Sarkar, S; Bhattacharjee, D; Hussain, Syed Arshad
Abstract: Polydiacetylens (PDAs) have attracted great attention for application in sensing field due to their unique fluorescence and colorimetric properties. Polydiacetylenes (PDAs) are important class of polymer that exists in two distinct phases namely metastable, non-fluorescent blue phase and stable, auto-fluorescent red phase under specific conditions. PDA is obtained through polymerization of diacetylene (DA) monomers, typically using UV irradiation that leads to photopolymerization of the diacetylene lipids. Herein, the diacetylene monomer 10, 12-tricosadiynoic acid (TCDA) and N-1-hexadecyl Imidazole have been used to prepare mixed films onto a filter paper surface using the self-standing technique and then polymerizes the mixed films to get blue phase by UV irradiation. The PDA and N-1-hexadecyl Imidazole mixed films in the blue phase exhibit rapid colorimetric/fluorescence response upon exposure to various volatile organic analytes. The colorimetric and fluorogenic responses of TCDA and N-1-hexadecyl Imidazole mixed films were investigated by UV-vis absorption spectroscopy, inverting fluorescence microscopy and RGB analysis. This study demonstrates that PDA and N-1-hexadecyl Imidazole mixed films can be a used for detection of various volatile organic analytes even in naked eye.